Heavy Metal Accumulation as Phytoremediation Potential of Aquatic Macrophyte, Monochoria vaginalis (Burm.F.) K. Presl Ex Kunth - Talukdar, Tulika; Talukdar, Dibyendu (International Journal of Applied Sciences and Biotechnology, 2015)
Bioaccumulation potential of six ecotypes, collected from six different industrial zones of lower Indo-Gangetic basin of West Bengal, India,of Monochoria vaginalis, commonly known as oval-leafed pondweed has been investigated based on chromium (Cr), cadmium (Cd) andCopper (Cu) accumulation pattern in different plant organs. Bioaccumulation potential was assessed by bioaccumulation factors (BFs-leavesmetal concentration/soil metal concentration), bioconcentration factors (BCFs- roots metal/soil metal), transfer factors (TFs-leaves +rhizomes/roots) and enrichment factors (EFs-metals in edible parts/soil metal). Accumulation pattern significantly differed among ecotypes,and accumulation in plant organs was highly metal-specific. BFs for Cr and Cd were >>1 in most of the ecotypes while high TFs (>>1) werenoticed in six ecotypes for Cr and Cu. BCFs was >>1 in all the ecotypes for Cd accumulation only. EFs values for the three metals hoveredaround 1 but it was > 1.0 for Cu in all the six ecotypes. The results suggested that Cr and Cu predominantly accumulated in leaves and rhizomeswhile Cd was predominantly sequestered in roots of M. vaginalis ecotypes. Cu, a redox active metal, showed higher capability than Cd and Crto accumulate in edible parts. In the present study, potential plant parts in M. vaginalis have been identified as bioaccumulation organs withoutany apparent symptoms of toxicity which can be used as phytoremediation of heavy metal contamination in aquatic ecosystems of lower Indo-Gangetic basin of India. DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.12193 Int J Appl Sci Biotechnol, Vol. 3(1): 9-15